Utilization of Digital Smart Board Technology to Increase Students' Interest in Learning at the Darussalamah Nurul Amin Foundation, East Lombok - Suhayyatman; Zulkieflimansyah; Supriadi (Cigarskruie: Journal of Educational and Islamic Research, 2025)
This study aims to analyze the utilization of digital Smart Board technology in enhancing students’ learning interest at Yayasan Darussalamah Nurul Amin, East Lombok. The background of this research is rooted in the increasing need for educational institutions to integrate interactive learning technologies in order to create more engaging, effective, and digitally aligned learning experiences. This study employed a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation of learning activities involving the use of the Smart Board. The results indicate that the use of the Smart Board significantly improves students’ interest in learning by providing more visual, interactive, and communicative learning materials. Features such as multimedia displays, simulations, touch-screen interactivity, and various digital learning applications encourage greater student engagement and participation. Teachers also reported that the Smart Board facilitates content delivery and classroom management. Supporting factors contributing to the effective use of this technology include adequate facilities, teachers’ competencies in operating the device, and students’ readiness to engage with digital tools. The study concludes that the integration of the Smart Board has a substantial impact on increasing students’ learning interest at Yayasan Darussalamah Nurul Amin, East Lombok. Recommendations include enhancing teacher training, developing relevant digital content, and maintaining technological devices to ensure optimal and sustainable use of digital learning tools.